Rancang Bangun Sistem Otomasi Monitoring Level Air Bendungan Untuk Pengendalian Banjir - subianto subianto; Paulus Lucky Tirma Irawan; Shenata Hanadam Shienjaya (SMATIKA JURNAL : STIKI Informatika Jurnal, 2019)
Along with the development of technology the problems that have never been separated from Indonesian society in general are floods. Flooding is a natural phenomenon that occurs because of the overflow of water in sewers, rivers or lakes that cannot accommodate water discharge. Floods occur because of the delay in the officers opening the floodgate. The lack of current dam supervisors has resulted in the monitoring of dams not being able to be carried out maximally, this has caused flooding due to the delay in setting the floodgates. In this study the author designed a dam water level monitoring automation system for flood control. The device used is the Raspberry Pi as a device that receives water level height data taken by the HC-SR04 ultrasonic sensor. The results of the ultrasonic sensor test get an average of the calculation of MSE (Mean Square Error) is 0.35 cm which is getting closer to the value of 0 indicates that the results of the accuracy of the ultrasonic sensor can be said to be accurate, the average error of 4,71% the sensor shows accuracy that very good with a deviation of 5.16% which is close to the average error, the range of data from the test results is quite accurate